Distribution of Sports Use in Sari City from the Perspective of Creative City Strategy - Taghi Ashouri; Masoumeh Kalateh Seifari; Hamidreza Ghezelseflou (تحقیقات کاربردی علوم جغرافیایی)
The purpose of the present research is to investigate the distribution of sports use in Sari with a creative city approach along improve citizen’s enjoyment of sports spaces in Sari. Due to the present research and analyzed components, the research type is applied and the method of doing it, is descriptive-analytical according to the nature of work and concerning the same method, was accomplished the distribution of sport use in Sari city from the viewpoint of creative city approach. The method of collecting library and documentary information and conducting interviews and field observations and the research-made questionnaire were also used. This questionnaire was randomly distributed among 400 users of sports places and equipment in Sari neighborhoods in 31 items of 6 dimensions. The collected data were analyzed by SPSS and smart PLS (3) statistical softwares. The findings showed, the relationship between the distribution of Sari sports use with dimensions (social, sports, cultural, physical, communicational and entrepreneurship) and also every dimension’ relationship with its criteria is positive and significant and the criterion of goodness of fit model is (GOF = 0.611(. As a result, the overall research model fit is well and the model structure fits well with data. Therefore, in order to achieve high utilization of Sari city spaces with creative city approach, it is recommended that city managers use citizen’s opinions and suggestions to provide plans in sports and using the art and attention to ancient sports cultures and the revival to create creativity in Sari city.